PERANCANGAN ALAT PENGOLAHAN SISTEM ANAEROB UP FLOW FILTER UNTUK ANALISIS LIMBAH CAIR INDUSTRI TAHU - Hadi Prasetyo Suseno; Paramita Dwi Sukmawati (PROSIDING SNAST, 2018)
This study aims to design an Anaerobic Up Flow Filter system processing tool. This tool is used to analyze the liquid waste of tofu industry which is used to determine differences in levels of BOD, COD, and SS before and after processing. This tool is also used to determine the effect of variations in processing debit and processing capability of the Anaerobic Up Flow Filter system on decreasing levels of BOD, COD, and SS according to applicable quality standards. The collection of tofu wastewater used the method for a moment in dry season. Verification of processing results is carried out at Environmental Engineering Laboratory of IST AKPRIND Yogyakarta. BOD levels after processing on all filter media were still above the quality standard threshold according to DIY Governor Decree No. 281 / KPTS / 1998. While the levels of COD and SS in activated charcoal filter media are still above the quality standard threshold according to DIY Governor Decree No. 281 / KPTS / 1998. The design of this tool produced a significant difference, namely the effect of discharge variation on Anaerobic Up Flow Filter processing are BOD 90.13%, COD 95.81% and SS 88.53%. The filtered sand and gravel media results result in meeting the quality standards, but for filter media the activated charcoal has not met quality standards.